PENDEKATAN GURU SEJARAH DALAM IMPLEMENTASI PENDIDIKAN KARAKTER: STUDI DESKRIPTIF DI SMA NEGERI 4 BENGKULU SELATAN - Een Syaputra; Ririn Selvianti (Jurnal Pendidikan, 2021)
This study aims to describe and analyze the approach of history teachers in the implementation of character education at SMA Negeri 4 Bengkulu Selatan. This study used a qualitative research design with a descriptive tife. This research was conducted at SMA negeri 4 Bengkulu Selatan. Dara were collected by in-depth inteviews, document analysis and observation. The data analysis was carried out using Milleas & Huberman’s Interactive Model, which consists of three stages: data reduction, data presentation, and conclution. Based on the research that has been done, the following results were fount: 1) the implementation od character education in history learning at SMA Negeri 4 Bengkulu Selatan was carried out using two main approach, namely the integrated learning approach and habituating approach; 2) an integrated approach to learning is carried out with four main strategies, namely value analysis, value clarification, storytelling method and cooperative learning model; 3) the habituating approach is carried out with three main strategies, namely praying before and after stuying, time discipline, and shaking hand.